Potential Use of Biochar in Growing Media. Issue 6 (31st October 2014) - Nemati, M. Reza; Simard, Frederic; Fortin, Jean-Pierre; Beaudoin, Jacynthe
Abstract : One of the greatest challenges in the growing media (GM) industry is sourcing superior quality, inexpensive, readily available, and environmentally friendly constituents. Biochar has been widely considered for its potential use in agriculture, in the energy sector, and for environmental purposes, but little attention has been paid to the use of biochar in GM. The objective of this study was to evaluate the potential use of biochar as an alternative for aggregates (e.g., perlite) and peat moss in the GM industry. A laboratory experiment was conducted comparing five organic substrates composed of different combinations of peat moss, perlite, and three types of biochar. The main physical and chemical properties of the biochars and organic substrates were measured. A leaching experiment was also performed to evaluate the nutrient‐holding capacity of the investigated substrates. Biochar showed a good potential for replacement of perlite and, to a lesser extent, peat moss in GM. Biochar increases cation‐exchange capacity (CEC) and pH, and it decreases nutrient leaching (11% reduction) in GM. Biochar affected the physical properties of GM, and this was mainly related to its particle‐size distribution (PSD). In spite of all of its benefits, biochar is still not a standardized product, and its properties may differ from one source to another. However, the GM industry requires high quality, homogeneous, and consistent components. To define suitable properties for biochar products in the GM industry, a standardization program should be put in place. Economically, biochar presents a greater potential in the replacement of aggregates than peat moss. Special attention should be paid to the presence of fine dust particles in some biochar.